A Practical Coordinated Trajectory Tracking for A Group of Mixed Wheeled Mobile Robots with Communication Delays - Sisdarmanto Adinandra; Dwi Ana Ratnawari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Coordination between a specific mobile robot type has been widely investigated, e.g coordination between unicycles. To extend the applicability of the system, a coordinated trajectory tracking of mixed type of mobile robots is considered. We prove that if a certain type of wheeled mobile robot is able to individually track its own reference, then coordination in tracking with other type of robots can be achieved simply by sharing individual tracking errors. Using two types of wheeled mobile robots, namely unicycle type (a nonholonomic mobile robot) and omni wheels type (a holonomic mobile robot), a coordinated control algorithm can achieve a global asymptotically stable condition of the error dynamics of the systems. Under bidirectional communication between robots as a constraint, the group is able to maintain individual tracking while coordinating the movements with other robots regardless occurring perturbations in the system and delays in communication channels. Simulation results suggest that information sharing between the robots increase the robustness in coordinating individual trajectories. Results also show that delays cause drop in performance similar to the case of no information sharing.